Age at surgery is not a prognostic factor for the AdVance‐XP male sling efficacy: A post‐hoc analysis of a prospective 7‐year multicentric study. Issue 6 (3rd June 2021) - Mumm, Jan‐Niclas; Abrarova, Benazir; Schütz, Julius; Klehr, Benedikt; Rodler, Severin; Vilsmaier, Theresa; Gozzi, Christian; Rehder, Peter; May, Florian; Homberg, Roland; Gebhartl, Peter; Stief, Christian G.; et al.
Abstract: Objective: To evaluate the factor age at the surgery on long‐term postoperative outcomes in patients with postprostatectomy incontinence (PPI) after AdVance XP transobturator male sling implantation. Methods: A total of 115 male patients with PPI, who had undergone AdVance XP sling implantation, were included. Patients had PPI with endoscopically confirmed good sphincteric‐contractility and a positive coaptive response. Kruskal–Wallis test with Dunn post‐hoc tests were used to analyze the postoperative outcome differences between the patient groups aged less than 66, 66–75, and over greater than 75 years. Outcome measures were the 24 h pad test, the number of daily pads used, the International Consultation on Incontinence Questionnaire short form (ICIQ‐SF), International Quality of Life Score (IQOL), Patient Global Impression of Improvement (PGI‐I), International Index of Erectile Function‐5 (IIEF‐5), International Prostate Symptom Score (IPSS), and Visual Analog Scale scores. Observation time points were 3, 6, 12, 24, 36, 48, 60, and 84 months after surgery. Results: Between the age groups, there was no difference in the success rate of the procedure (defined as 0 pads/24 h and less than 5 g in the 24‐h pad test) at any point in time. Subjective parameters measures using the ICIQ‐SF, PGI‐I, IQOL, and IPSS scores showed no differences between the two cohorts. Only erectile function (IIEF‐5 score) was lower in older patients in comparison to the cohort aged less than 66 years ( p  < 0.05 at 3, 6, 12, 24, 36, and 48 months). Conclusions: The present study complements the European multicentre AdVance XP follow‐up study. Here, we show that age at surgery does not affect the objective success, subjective success, or the complication rate. Thus, we do not recommend factoring in chronological age into surgical selection criteria for the AdVance XP implantation.